Risk Factors Associated with Ventricular Peritoneal Shunt Infections and their Clinical Outcome in Children: A Case-Control Study of the Past 5 Years - Waqar Ahmed, Ms. Apsara Ali Nathwani, Falak Abro, Wajid Hussain, Ayesha Yasir, fatima mir (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the risk factors associated with the development of ventricular peritoneal shunt infection and time to infection, as the number of days from most recent shunt intervention to the diagnosis of the infection and clinical outcomes and the antimicrobial susceptibility pattern in children admitted with the ventricular peritoneal shunt. Study Design: Retrospective case-control study Place and duration of study: Aga Khan University Hospital Karachi, Pakistan between January 2015 to December 2020 Results: A total of 460 patients of ages 0-20 years with ventricular peritoneal shunt were selected. Out of 460, 52 individuals met the criteria of the case and were recruited for the study. The findings from multivariable logistic regression, after accounting for potential confounding factors, indicated that the odds of shunt infection were extremely high for patients undergoing surgery in the current admission (adjusted OR 167.3, 95% CI: 8.96 – 3130.86). Likewise, the odds of infection were approximately 12 times more for patients with fever (95% CI: 1.28 – 113.26) and tory of shunt removal (95% CI: 2.06– 67.20). Conclusion: Through a thorough analysis of medical records, the study revealed that several risk factors, such as younger age, previous shunt infections, surgery in current admission, shunt removal/replacement, previous revisions, current complication and fever were associated with a higher risk of shunt infection. Keywords: Risk factors, ventricular peritoneal, shunt infections, clinical outcome,